2004
DOI: 10.1159/000077398
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genetic Polymorphisms of the Renin-Angiotensin System on IgA Nephropathy

Abstract: Background: We evaluated the impact of the three major genetic polymorphisms of the renin-angiotensin system [angiotensinogen (AGT) gene M235T, angiotensin-converting enzyme (ACE) gene-I/D and angiotensin II-type 1 receptor (AT1R) gene A1166C polymorphisms] as risk factors in IgA nephropathy. Methods: The clinical course of 107 patients with biopsy proven IgA nephropathy followed up for 6.6 ± 5.8 years was examined. The genetic polymorphisms were determined by PCR amplification. Results: The allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 51 publications
(74 reference statements)
0
36
2
1
Order By: Relevance
“…In accordance with our findings, two earlier studies, including 260 110 and 168 140 Caucasian patients with various non-diabetic renal diseases, reported a deleterious effect of the D allele on loss of renal function only or particularly present in patients with the MM genotype of the angiotensinogen-M235T polymorphism. In contrast, Bantis et al 141 found a negative impact of the combination of D and T alleles on loss of calculated deterioration of renal function in patients with IgA nephropathy (n=44). Studies of single gene effects on the response to RAS blockade in hypertensive patients 129 and in patients with hypertension and left ventricular hypertrophy 142 supports the identification of the M allele of the angiotensinogen-M235T and the A allele of the AT 1 -receptor (A 1166 →C) polymorphisms as risk alleles.…”
Section: Genetic Interaction and Pharmacogenomicsmentioning
confidence: 80%
“…In accordance with our findings, two earlier studies, including 260 110 and 168 140 Caucasian patients with various non-diabetic renal diseases, reported a deleterious effect of the D allele on loss of renal function only or particularly present in patients with the MM genotype of the angiotensinogen-M235T polymorphism. In contrast, Bantis et al 141 found a negative impact of the combination of D and T alleles on loss of calculated deterioration of renal function in patients with IgA nephropathy (n=44). Studies of single gene effects on the response to RAS blockade in hypertensive patients 129 and in patients with hypertension and left ventricular hypertrophy 142 supports the identification of the M allele of the angiotensinogen-M235T and the A allele of the AT 1 -receptor (A 1166 →C) polymorphisms as risk alleles.…”
Section: Genetic Interaction and Pharmacogenomicsmentioning
confidence: 80%
“…The role of two genes variants of angiotensinogen (AGT) and angiotensin II type-1 receptor (AT1R) and their interaction with ACE I/D polymorphism on the susceptibility to DN has been investigated with controversy (47)(48)(49)(50).…”
Section: Interaction Between Ace I/d and Variants Of Ras Genesmentioning
confidence: 99%
“…[3,11,12,13] DD genotype has been postulated as a risk factor in renal diseases. DD genotype has been shown to be associated with FSGS with declining renal function.…”
Section: Discussionmentioning
confidence: 99%